Sequence and functional analyses of Haemophilus spp. genomic islands. - Juhas, M; Power, P; Harding, R; Ferguson, D; Dimopoulou, I; Elamin, A; Mohd-Zain, Z; Hood, D; Adegbola, R; Erwin, A; Smith, A; Munson, R; et al. (2007)
BACKGROUND: A major part of horizontal gene transfer that contributes to the diversification and adaptation of bacteria is facilitated by genomic islands. The evolution of these islands is poorly understood. Some progress was made with the identification of a set of phylogenetically related genomic islands among the Proteobacteria, recognized from the investigation of the evolutionary origins of a Haemophilus influenzae antibiotic resistance island, namely ICEHin1056. More clarity comes from this comparative analysis of seven complete sequences of the ICEHin1056 genomic island subfamily. RESULTS: These genomic islands have core and accessory genes in approximately equal proportion, with none demonstrating recent acquisition from other islands. The number of variable sites within core genes is similar to that found in the host bacteria. Furthermore, the GC content of the core genes is similar to that of the host bacteria (38% to 40%). Most of the core gene content is formed by the syntenic type IV secretion system dependent conjugative module and replicative module. GC content and lack of variable sites indicate that the antibiotic resistance genes were acquired relatively recently. An analysis of conjugation efficiency and antibiotic susceptibility demonstrates that phenotypic expression of genomic island-borne genes differs between different hosts. CONCLUSION: Genomic islands of the ICEHin1056 subfamily have a longstanding relationship with H. influenzae and H. parainfluenzae and are co-evolving as semi-autonomous genomes within the 'supragenomes' of their host species. They have promoted bacterial diversity and adaptation through becoming efficient vectors of antibiotic resistance by the recent acquisition of antibiotic resistance transposons.